CRISPR-C: circularization of genes and chromosome by CRISPR in human cells. Issue 22 (24th August 2018) - Møller, Henrik Devitt; Lin, Lin; Xiang, Xi; Petersen, Trine Skov; Huang, Jinrong; Yang, Luhan; Kjeldsen, Eigil; Jensen, Uffe Birk; Zhang, Xiuqing; Liu, Xin; Xu, Xun; Wang, Jian; et al.
Abstract: Extrachromosomal circular DNA (eccDNA) and ring chromosomes are genetic alterations found in humans with genetic disorders. However, there is a lack of genetic engineering tools to recapitulate and study the biogenesis of eccDNAs. Here, we created a dual-fluorescence biosensor cassette, which upon the delivery of pairs of CRISPR/Cas9 guide RNAs, CRISPR-C, allows us to study the biogenesis of a specific fluorophore expressing eccDNA in human cells. We show that CRISPR-C can generate functional eccDNA, using the novel eccDNA biosensor system. We further reveal that CRISPR-C also can generate eccDNAs from intergenic and genic loci in human embryonic kidney 293T cells and human mammary fibroblasts. EccDNAs mainly forms by end-joining mediated DNA-repair and we show that CRISPR-C is able to generate endogenous eccDNAs in sizes from a few hundred base pairs and ranging up to 207 kb. Even a 47.4 megabase-sized ring chromosome 18 can be created by CRISPR-C. Our study creates a new territory for CRISPR gene editing and highlights CRISPR-C as a useful tool for studying the cellular impact, persistence and function of eccDNAs.